2020
DOI: 10.15446/av.enferm.v38n2.78690
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of delirium in children admitted into the Intensive Care Unit: psCAM-ICU Tool

Abstract: Background: Delirium has been identified as a risk factor for the mortality of critically ill patients, generating great social and economic impacts, since patients require more days of mechanical ventilation and a prolonged hospital stay in the intensive care unit (ICU), thus increasing medical costs. Objective: To describe the prevalence and characteristics of delirium episodes in a sample of 6-month to 5-year-old children who are critically ill. Methods: Cohort study at a Pediatric Intensive Care Unit (PICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 25 publications
3
12
0
1
Order By: Relevance
“…Twenty-seven (16, 18–22, 35, 38–43, 45–59) were prospective in design, two retrospective (36, 37), and two point prevalence (44, 58). Twenty-seven were single-center studies (16, 18–21, 36–43, 45–57, 59), and four were multicenter studies (22, 35, 44, 58), including two multisite point prevalence studies (44, 58). Twenty-seven took place in a PICU (16, 18–22, 35–43, 45–49, 52–54, 56–59), two in a PCICU (51, 55), one in a mixed PICU and PCICU (50), and one across multiple PCICUs or PICUs (44).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-seven (16, 18–22, 35, 38–43, 45–59) were prospective in design, two retrospective (36, 37), and two point prevalence (44, 58). Twenty-seven were single-center studies (16, 18–21, 36–43, 45–57, 59), and four were multicenter studies (22, 35, 44, 58), including two multisite point prevalence studies (44, 58). Twenty-seven took place in a PICU (16, 18–22, 35–43, 45–49, 52–54, 56–59), two in a PCICU (51, 55), one in a mixed PICU and PCICU (50), and one across multiple PCICUs or PICUs (44).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven were single-center studies (16, 18–21, 36–43, 45–57, 59), and four were multicenter studies (22, 35, 44, 58), including two multisite point prevalence studies (44, 58). Twenty-seven took place in a PICU (16, 18–22, 35–43, 45–49, 52–54, 56–59), two in a PCICU (51, 55), one in a mixed PICU and PCICU (50), and one across multiple PCICUs or PICUs (44). No stand-alone NICU studies were found, but 18 included neonates (18, 36–38, 40–46, 50, 51, 53–56, 58).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several challenges associated with accurately and systematically diagnosing pediatric delirium. The gold standard for identifying delirium is a diagnosis by a child and adolescent psychiatrist based on criteria of the Diagnostic and Statistical Manual of Mental Disorders 6,7. Delirium in hospitalized children is characterized as hypoactive, hyperactive, or mixed.…”
mentioning
confidence: 99%
“…Delirium occurs in infants as young as three months old and may not have upper or lower age limitations. In some instances, parents may describe their child's behavior as "this is not my child" and should be taken seriously because this behavior change may be an additional indication of delirium 7. Management of a child with delirium begins with identifying and modifying factors that contribute to the development of delirium in children, including hypoxia, medications such as anticholinergics and benzodiazepines, metabolic disturbances, pain, and anxiety.Anesthesia impact on emergency deliriumAnesthesia emergence delirium (AED) is a transient state of irritation and dissociation, which occurs after discontinuation of anesthesia in some patients and is not responsive to consolation.…”
mentioning
confidence: 99%